Gambaran Antenatal Care (Anc) Ibu Hamil Di Klinik Latifa Kelurahan Kedaung Selama Bulan Juli 2024 - Rahma Rufaida Susetyo (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Introduction : Maternal Mortality Rate (MMR) remains a global health challenge, particularly in low and middle income countries. This study aims to describe the characteristics of pregnant women receiving Antenatal Care (ANC) services at Latifa Klinik, Kelurahan Kedaung, during July 2024. Objective : A descriptive method was used with a total sampling technique, involving 50 respondents. Data were analyzed descriptively using a checklist of variables such as age, education, occupation, and parity. Results : Most pregnant women were aged 20-35 years (82%), had a high school education (74%), were unemployed (66%), and had 2-4 children (58%). These factors influenced the regularity and quality of ANC services received. Pregnant women in the ideal age range (20-35 years) had a lower risk of pregnancy complications, while higher education levels supported greater awareness and knowledge about the importance of ANC. Additionally, the mothers' occupational status and parity contributed to the regularity of ANC visits. Conclusion : That more intensive health education, improved access to ANC services, and special attention to high-risk pregnant women are essential to reducing MMR. These efforts are crucial for achieving the Sustainable Development Goals (SDGs) target of a global MMR below 70 per 100,000 live births by 2030.